2019
DOI: 10.1016/j.rvsc.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

The 3D8 single chain variable fragment protein suppress infectious bronchitis virus transmission in the transgenic chickens

Abstract: Infectious bronchitis (IB) generated by the infectious bronchitis virus (IBV) causes economic difficulties for livestock farmers. The 3D8 single chain variable fragment (scFv) protein is a recombinant antibody with nuclease activity that shows antiviral effects against various DNA and RNA viruses in mice and chickens. In this experiment, 3D8 scFv G 2 transgenic chickens produced by crossing 3D8 scFv G 1 transgenic rooster and wild type hens were screened by genomic PCR and immunohistochemistry analysis. 3D8 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…3D8 scFv is also used in Lactobacillus paracasei ( L. paracasei ) for the use of this bacterium as a feed additive ( Hoang et al, 2015 ). TG chickens ubiquitously expressing the 3D8 scFv gene were developed, and they were verified as avian models showing nuclease activity ( Byun et al, 2017 , 2020 ; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D8 scFv is also used in Lactobacillus paracasei ( L. paracasei ) for the use of this bacterium as a feed additive ( Hoang et al, 2015 ). TG chickens ubiquitously expressing the 3D8 scFv gene were developed, and they were verified as avian models showing nuclease activity ( Byun et al, 2017 , 2020 ; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As overexpression of the 3D8 scFv gene induced degradation of host nucleic acids ( Jang et al, 2009 ), the chicken beta-actin promoter in TG chickens was used, and 3D8 scFv mRNA and the encoded protein were detected in all organ tissues and in isolated chicken embryonic fibroblast cells. 3D8 scFv TG chickens showed antiviral activity against H9N2 low-pathogenic avian influenza virus ( AIV ), and further studies showed similar activity against infectious bronchitis virus ( IBV ) and Newcastle disease virus ( NDV ) ( Lee et al, 2019 ; Byun et al, 2020 ). In addition, chickens fed Lactobacillus species expressing 3D8 scFv showed improved growth performance and immune homeostasis ( Sureshkumar et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Novel human coronaviruses have emerged during the past two decades [ 3 , 27 ]. The COVID-19 outbreak occurred in late December in Wuhan (China) and rapidly became a global pandemic [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…3D8 is a unique scFv that possesses a broad-spectrum nuclease activity and confers antiviral protection from a variety of viruses including DNA and RNA viruses (Figure 5) ( 28, 29 ). 3D8 scFv previously showed the antiviral effect against infectious Bronchitis virus, a member of gammacoronaviruses in transgenic chickens expressing 3D8 scFv ( 24 ). The antiviral activity of 3D8 scFv against SARS-CoV-2 and other coronaviruses remained to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…3D8 exhibited in vivo antiviral therapeutic effects against PRV in C57BL/6 mice. The transmission of avian influenza and bronchitis viruses was suppressed in transgenic chickens expressing the 3D8 scFv (23)(24)(25)(26). However, the antiviral activity of the 3D8 scFv against SARS-CoV-2 and other coronaviruses remains unknown.…”
Section: Introductionmentioning
confidence: 99%